Digital behaviour change interventions to facilitate physical activity in osteoarthritis: a systematic review. (4th May 2018) - Berry, Alice; McCabe, Candy S.; Muir, Sarah; Walsh, Nicola
Abstract : Background: Digital behaviour change interventions (DBCIs) might offer an opportunity to support people with osteoarthritis (OA) to self-manage and monitor their levels of physical activity (PA). Objectives: To determine the effectiveness of DBCIs for increasing physical activity in people with OA; to identify theory and techniques used; to examine outcome measures for physical activity; to document how uptake and usage is reported. Methods: Electronic databases were searched up to July 2017. Interventions for adults with OA, which aimed to increase levels of physical activity, delivered via a digital platform, were included. Results: Nine studies met the inclusion criteria. Six reported significant increases in physical activity. Interventions were mostly based on Social Cognitive Theory. Numerous behaviour change techniques (BCTs) were used. Most common physical activity outcomes measures were; self-reported aerobic exercise and self-reported strengthening exercises. Two studies used wearable activity monitors. A wide variety of methods were employed to report uptake and usage of DBCIs. Conclusions: Existing DBCIs can have a short-term positive effect on levels of physical activity in this population, but it remains unclear how effective they might be, over a longer period of time. It is vital to document and evaluate how individual components influence the outcome and effectiveness of an intervention. Future interventions should identify BCTs used in the development stages, and use valid measures of both physical activity, and intervention usage, so that results are transparent and comparable.